DENTAL AND ORAL HEALTH SCREENING FOR CHILDREN IN KELURAHAN SIMOKERTO, SURABAYA - Darmadi, Eveline Yulia; Fauziah, Yessy Andriani; Ramadhani, Salma; Budi, Nasya Kamila Mutiara (LPPM Univ. Ibn Khaldun Bogor, 2024)
Abstract. Oral health issues in children are a significant global public health concern. Factors such as dietary habits, socioeconomic status, and level of knowledge affect the prevalence of dental caries, periodontal diseases, and other oral health conditions. In Indonesia, especially in urban areas like Surabaya, growing attention is paid to children's oral health. This study aimed to assess children's dental and oral health status in Kelurahan Simokerto, Surabaya, and identify associated risk factors. The sample is 38 children aged 3-11 years in Kelurahan Simokerto. Data were gathered through clinical exams. Results showed a high prevalence of dental caries and poor oral hygiene practices, such as infrequent brushing and limited flossing. Socioeconomic factors, including parental education and household income, were linked to the children's oral health status. These findings highlight the need for targeted oral health promotion programs in Kelurahan Simokerto, focusing on improving oral hygiene practices, encouraging regular dental check-ups, and addressing socioeconomic determinants of oral health. The study highlights the need for long-term, community-driven interventions to address dental caries and improve oral health outcomes, as short-term efforts showed no significant changes in DEFT and OHIS frequencies in Kelurahan Simokerto.